Combined Fainting and Psychogenic Non-epileptic Seizures as Significant Therapy Hurdles in Blood-Injury-Injection Phobia: A Mini-Review and Case Report - von Mücke-Heim, Iven-Alex; Walter, Isabelle; Nischwitz, Sandra; Erhardt, Angelika (Frontiers in Psychiatry, 2022)
Background: Anxiety disorders are the most frequent mental disorders. Among the different subtypes, specific phobias are the commonest. Due to the ongoing SARS-CoV-19 pandemic, blood-injury-injection phobia (BII) has gained wider attention in the context of large-scale vaccination campaigns and public health. In this BII phobia mini-review and case report, we describe the successful treatment of a severe BII phobia case with combined fainting and psychogenic non-epileptic seizures and demonstrate the role of specialized outpatient care. Case Report: The patient was a 28-year-old woman. She suffered from intense fear and recurrent fainting with regard to needles, injections, injuries, and at the sight of blood since early childhood. Medical history revealed infrequent psychogenic non-epileptic seizures (PNES) following panic attacks after sustained exposure to phobic stimuli. Family history was positive for circulation problems and BII fears. Psychopathological evaluation confirmed BII phobia symptoms and diagnosis was made according to the DSM-5. The Multidimensional Blood/Injury Phobia Inventory short version (MBPI-K) revealed severe manifestation of the disease. Neurological examination was ordinary. Repeated electroencephalography detected no epileptic pattern. Cranial magnetic resonance imaging showed normal morphology. Treatment was carried out by a seasoned, multidisciplinary team. Cognitive behaviour therapy and exposure were performed. Modification of standard treatment protocol was necessary due to hurdles posed by recurrent fainting and a severe panic-triggered dissociative PNES during in vivo exposure. Modification was implemented by limiting in vivo exposure intensity to moderate anxiety levels. In addition to applied muscle tension and ventilation techniques, increased psychoeducation, cognitive restructuring, and emotion regulation skills (e.g., ice pack, verbal self-instructions) were used to strengthen the patient’s situational control during in vivo exposure. A total of 15 sessions was performed. Therapy success was proven by 83% reduction in MBPI-K rating, SARS-CoV-19 vaccination, and a blood draw without psychological assistance, fainting, or seizure. Conclusion: Taken together, this case demonstrates the potential of and need for specialized outpatient care and individualized treatment for severe BII phobia patients in order to provide them the perspective to have necessary medical procedures done and get vaccinated.